Pengaruh Ukuran Dewan Komisaris, Proporsi Komisaris Independen, Kepemilikan Manajerial, Kepemilikan Institusional, Dan Komite Audit Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Muhammad Isya Cholillah; Rina Trisnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study is to analyze whether the board size, proportion of independent commissioners, managerial ownership, institutional ownership, and audit committee size influence corporate social responsibility (CSR) disclosure in banking companies. The population of this study consists of banking companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2021, totaling 46 companies. This research uses secondary data obtained from the annual reports of companies listed on the IDX from 2018 to 2022. After adjusting for purposive sampling criteria, the total sample obtained is 44 companies. Data collection is conducted using documentation method with multiple linear regression analysis technique. The research results show that the Board of Commissioners, Institutional Ownership, and Audit Committee have a significant influence on Corporate Social Responsibility (CSR) in banking companies listed on the BEI in 2018-2021, in accordance with agency theory. However, the proportion of independent commissioners and managerial ownership do not have a significant influence on CSR, in line with legitimacy theory.